Leaflets of the ball room. Being a sketch of the polka quadrilles, the Baden, mazurka figures &c. &c. to which is appended the music of the celebrated Redowa waltz, now first published in the United States. (Philadelphia, New York, Turner & Fisher, 1847)
Compiled by a publisher and small enough to fit into a pocket, this manual gives directions for polka quadrilles, mazurka quadrilles, and "The New Redowa," all "as taught by Mr. Durang and daughter." Other dances include a waltz cotillion, gallopade quadrille, and Spanish Dance.
At head of t.-p.: "The poetry of motion."
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; Redowas; Dance Instruction and Technical Manuals